Job satisfaction and Burnout syndrome in teachers during confinement due to the COVID-19 pandemic - Cortez Silva, Daisy Mily (2021)
The work overload that teachers present in the current context is a risky situation, since it can generate prolonged states of stress causing a burnout syndrome and affecting their job satisfaction. The objective was to determine the significant relationship between job satisfaction and the components of burnout syndrome during confinement due to the COVID-19 pandemic. The study had a cross-sectional correlational design. 205 teachers participated, who answered the Job Satisfaction Scale for Teachers (ESLA-Education) and the Maslach Burnout Inventory (MBI). The results indicate a statistically significant inverse correlation between job satisfaction and the components of burnout syndrome: emotional exhaustion (rho =-.315; p = .000), depersonalization (rho =-.252; p = .000) and achievement personal (rho =-.254; p = .000). It is concluded that teachers who present high emotional fatigue, loss of sensitivity and empathy, deterioration of their abilities and a feeling of failure show job dissatisfaction. Therefore, it is necessary to have protective factors to prevent emotional distress for teachers.